Tourism Destination Management Model In Mount Jae Campground As A Support Of Economic Growth For The Community Of Sedau Village, Narmada District, West Lombok District in 2020-2022 - Devi Febriana; Prayitno Basuki; Adhitya Bagus Singandaru (Jurnal Internasional Riset Bisnis Pariwisata, 2023)
The purpose of this study is to determine how the management model of Mount Jae Campground tourist destinations supports the economic growth of the people of Sedau Village, West Lombok. The type of research used, namely qualitative research and using a qualitative approach, is qualitative because the data is in the form of information on how the strategy of the Tourism Destination Management Model at Mount Jae Campground as Support for Economic Growth of the Sedau Village Community. Determining informants to interview uses two techniques, purposive and snowball. The data analysis technique used is the Miles and Huberman model. The model of Mount Jae Lake tourism management is in the following ways: (1) Increase the promotion of tourism objects so that they can be known by many tourists, not only local tourists but tourists outside the region and abroad. (2) Holding art/cultural activities to welcome tourists visiting Mount Jae tourist attractions, this method can attract tourists to visit. (3) Improve guide services for visiting tourists. (4) Improve facilities to support tourist activities in tourist destinations.